2018
DOI: 10.21873/anticanres.13026
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies for Pancreatic Cancer and Hurdles Ahead

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive and lethal cancers with a median survival of 6 months after diagnosis. Intrinsic resistance to chemotherapeutics and lack of effective targeted therapies are the major factors contributing to dismal prognosis. Several important genetic alterations (i.e., mutations, deletions) have been identified to be involved in the initiation and progression of pancreatic cancer, including KRAS and inactivation of tumor suppressors, such as TP53, SMAD4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 83 publications
0
64
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma (PDAC) has the lowest survival rate of all major cancers (∼6% at 5 years post-diagnosis) and is projected to become the second most common cause of cancer related death by 2030 (1,2). Intrinsic chemotherapyresistance is one of the major clinical problems associated with PDAC, resulting in the failure of currently available therapeutic options (3). Adjuvant chemotherapy in patients with resected PDAC has been shown to extend survival over surgery alone, and more recently, more intensive regimens such as FOLFIRONOX have been shown to be even more effective (4).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) has the lowest survival rate of all major cancers (∼6% at 5 years post-diagnosis) and is projected to become the second most common cause of cancer related death by 2030 (1,2). Intrinsic chemotherapyresistance is one of the major clinical problems associated with PDAC, resulting in the failure of currently available therapeutic options (3). Adjuvant chemotherapy in patients with resected PDAC has been shown to extend survival over surgery alone, and more recently, more intensive regimens such as FOLFIRONOX have been shown to be even more effective (4).…”
Section: Introductionmentioning
confidence: 99%
“…While mortality rates are declining for many cancers due to early detection and improved treatment, rates for PDAC are still rising (Siegel et al, 2018), promoting PDAC to the top three cancer killers within the next decade (Rahib et al, 2014). Standard PDAC treatment includes surgical resection and adjuvant chemotherapy with FOLFIRINOX or gemcitabine in combination with nab-paclitaxel providing the most promising results (Aslan et al, 2018). However, systemic chemotherapy is associated with severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Haas et al reported no significant difference in overall survival for KRAS wild-type vs. mutant patients, and KRAS mutation status is predictive rather than prognostic in advanced PC (34). Efforts focused on targeting PC have been disappointing (7,36), so the standard of care for PC continues to be chemotherapy. However, chemoresistance is a major challenge in the treatment of PC (14,15,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chemotherapy plays a critical role in the therapeutic management of PC in patients with unresectable PC (4)(5)(6). Recent years have witnessed the rapid development of revolutionary targeted therapies and immune therapies, but these therapies have not shown significant results in PC (7)(8)(9). Thus, cytotoxic drugs remain the backbone of treatment for PC.…”
Section: Introductionmentioning
confidence: 99%